2022
DOI: 10.1186/s12889-022-14786-2
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel analysis of individual- and community-level determinants of birth certification of children under-5 years in Nigeria: evidence from a household survey

Abstract: Promoting birth certification is central to achieving legal identity for all - target 16.9 of the 2030 Sustainable Development Goals. Nigeria is not on track to achieve this goal with its low coverage of birth certification (BC). This study is aimed at identifying patterns of BC and its associated individual- and community-level factors, using pooled cross-sectional data from three rounds (2008, 2013, and 2018) of the nationally representative Nigerian Demographic and Health Survey. A weighted sample of 66,630… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The study found that GDP has a positive significant effect on residential property development, while interest rate and inflation rate have negative significant effects (Olatunji & Adewusi, 2023). Anaduaka (2022) conducted a multilevel analysis using a two-level multilevel logistic model to identify patterns of birth certification and its associated individual-and community-level factors in Nigeria. The study identified several protective and risk factors which can be strategic areas for universal birth certification (Anaduaka, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that GDP has a positive significant effect on residential property development, while interest rate and inflation rate have negative significant effects (Olatunji & Adewusi, 2023). Anaduaka (2022) conducted a multilevel analysis using a two-level multilevel logistic model to identify patterns of birth certification and its associated individual-and community-level factors in Nigeria. The study identified several protective and risk factors which can be strategic areas for universal birth certification (Anaduaka, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Anaduaka (2022) conducted a multilevel analysis using a two-level multilevel logistic model to identify patterns of birth certification and its associated individual-and community-level factors in Nigeria. The study identified several protective and risk factors which can be strategic areas for universal birth certification (Anaduaka, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is an intriguing nding that such a large proportion of much older children received SMC medicines despite the obvious age difference between them and under-5 children. However, such children may not be distinguishable from under-5 children by mere physical appearance, due to the prevalence of malnutrition and stunting in the study setting, and SMC community distributors' di culty in ascertaining children's age due to absence of veri able home-based birth and civil registration records [8][9][10][11].From an operational perspective, however, administering SMC medicines to ineligible children presents a substantial challenge, particularly in terms of ensuring the availability of su cient SPAQ stock levels to reach the entire target population of eligible children. This has important implications for reaching and sustaining high target population coverage, while maintaining optimal levels of programmatic impact and effectiveness in SMC delivery settings.…”
Section: Discussionmentioning
confidence: 99%
“…However, in low and middle -income countries, civil registration and identi cation systems are often underdeveloped [8][9][10][11]. Coupled with the high prevalence of malnutrition and stunting in regions with high malaria attack rates, determining children's age with accuracy is therefore often challenging [6].…”
Section: Introductionmentioning
confidence: 99%
“…Eleven (11) explanatory variables were considered for inclusion into the study based on their availability in the DHS dataset as well their association with birth registration from previous studies (9,(16)(17)(18). We further segregated the variables into the individual level and the household/community level.…”
Section: Variablesmentioning
confidence: 99%